Association Between Prepregnancy Body Mass Index and Severe Maternal Morbidity. Issue 3 (September 2018) - Lisonkova, S.; Muraca, G.M.; Potts, J.; Liauw, J.; Chan, W.S.; Skoll, A.; Lim, K.I.
Abstract : ( JAMA 2017;318(18):1777–1786) Overweight and obesity are associated with increased risks of adverse maternal and neonatal events such as preterm birth, stillbirth, and neonatal or infant death; underweight is also associated with adverse outcomes. However, it is unclear if the risk of severe maternal morbidity increases as body mass index (BMI) increases. This study aimed to determine the association between prepregnancy BMI and severe maternal morbidity or mortality.